Risperidone increases the cortical silent period in drug-naive patients with first-episode schizophrenia: A transcranial magnetic stimulation study - Ustohal, Libor; Mayerova, Michaela; Hublova, Veronika; Prikrylova Kucerova, Hana; Ceskova, Eva; Kasparek, Tomas (Journal of psychopharmacology (Oxford, England), 2017)
OBJECTIVES: Schizophrenia is accompanied by impaired cortical inhibition, as measured by several markers including the cortical silent period (CSP). It is thought that CSP measures gamma-aminobutyric acid receptors B (GABAB) mediated inhibitory activity. But the mutual roles of schizophrenia as a disease and the drugs used for the treatment of psychosis on GABA mediated neurotransmission are not clear. METHODS: We recruited 13 drug-naive patients with first-episode schizophrenia. We used transcranial magnetic stimulation to assess CSP prior to initiating risperidone monotherapy and again four weeks later. At the same time, we rated the severity of psychopathology using the Positive and Negative Syndrome Scale (PANSS). RESULTS: We obtained data from 12 patients who showed a significant increase in CSP, from 134.20±41.81 ms to 162.95±61.98 ms ( p=0.041; Cohen's d=0.544). After the treatment, the PANSS total score was significantly lower, as were the individual subscores ( p<0.05). However, no correlation was found between ΔCSP and ΔPANSS. CONCLUSION: Our study in patients with first-episode schizophrenia demonstrated an association between risperidone monotherapy and an increase in GABAB mediated inhibitory neurotransmission.
Keywords: dospělí; antipsychotika; nervový útlum; Antipsychotic Agents; GABA; Adult; gamma-Aminobutyric Acid; Neural Inhibition; lidé; transkraniální magnetická stimulace; cortical silent period; psychotické poruchy; schizofrenie; risperidon; Risperidone; risperidone; Psychotic Disorders; Schizophrenia; nervový přenos; Synaptic Transmission; cortical inhibition; mozková kůra; Cerebral Cortex; Transcranial Magnetic Stimulation; transcranial magnetic stimulation; Humans